2021
DOI: 10.1200/op.20.00572
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Implementation of Telehealth Visits for Care of Patients With Cancer in Houston During the COVID-19 Pandemic

Abstract: PURPOSE: The purpose of this study was to evaluate the use of telemedicine amid the SARS-CoV-2 pandemic in patients with cancer and assess barriers to its implementation. PATIENTS AND METHODS: Telehealth video visits, using the Houston Methodist MyChart platform, were offered to patients with cancer as an alternative to in-person visits. Reasons given by patients who declined to use video visits were documented, and demographic information was collected from all patients. Surveys were used to assess the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 11 publications
13
114
0
1
Order By: Relevance
“…Findings reflected that the interviewees are slightly more satisfied with Telehealth compared to mHealth. These results regarding satisfaction contrasted with survey results, where participants identified with being slightly more satisfied with mHealth compared to Telehealth, supporting findings from [47][48][49][50]. Furthermore, in relation to future use prospects, Telehealth was identified to be a promising approach in reducing clinical visits, improving quality healthcare.…”
Section: Interview Resultssupporting
confidence: 52%
“…Findings reflected that the interviewees are slightly more satisfied with Telehealth compared to mHealth. These results regarding satisfaction contrasted with survey results, where participants identified with being slightly more satisfied with mHealth compared to Telehealth, supporting findings from [47][48][49][50]. Furthermore, in relation to future use prospects, Telehealth was identified to be a promising approach in reducing clinical visits, improving quality healthcare.…”
Section: Interview Resultssupporting
confidence: 52%
“…However, studies regarding costeffectiveness of telemedicine tend to depend on the context, and previous studies have sometimes failed to give conclusive data regarding cost-effectiveness [11][12][13][14]. Similarly, studies have shown high patient satisfaction for some contexts but not conclusive data in other contexts [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…For these, and other, reasons, patients have been very satisfied with the incorporation of telehealth into routine clinical practice. 5 …”
Section: Telemedicine: Opportunities and Pitfallsmentioning
confidence: 99%